2000
DOI: 10.1093/humupd/6.2.122
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and reproduction: gene damage to human gametes and embryos

Abstract: Assisted conception is a useful methodology for detecting disturbances in clinical outcome, meiotic maturation, and genetic integrity of human gametes. Germinal cells are vulnerable to genetic damage from smoking, but can repair damage during meiosis. In ejaculated spermatozoa, repair capacity declines drastically. Smoking alters the meiotic spindle of oocytes and spermatozoa, leading to chromosome errors which affect reproductive outcomes. Smoking is associated with reduced numbers of retrieved oocytes, leadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
209
1
10

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 347 publications
(229 citation statements)
references
References 121 publications
9
209
1
10
Order By: Relevance
“…Studies in mice have used a variety of techniques to determine the effects of heat stress on fertility and it is notable that similar disturbances in testicular function and reduced fertility have been recorded in animals housed at 36 8C for 12 or 24 h and those subjected to a transient scrotal heat stress at 42-43 8C for 20-60 min (Lue et al 1999, 2000, Rockett et al 2001, Setchell et al 2001, Banks et al 2005, Zhang et al 2005. Our study includes novel data on the origin of DNA damage found in sperm i.e.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Studies in mice have used a variety of techniques to determine the effects of heat stress on fertility and it is notable that similar disturbances in testicular function and reduced fertility have been recorded in animals housed at 36 8C for 12 or 24 h and those subjected to a transient scrotal heat stress at 42-43 8C for 20-60 min (Lue et al 1999, 2000, Rockett et al 2001, Setchell et al 2001, Banks et al 2005, Zhang et al 2005. Our study includes novel data on the origin of DNA damage found in sperm i.e.…”
Section: Discussionmentioning
confidence: 86%
“…in fathers who smoke, can be passed on to their children and has been linked with an increased incidence of childhood cancer in their offspring (Zenzes et al 1999, Zenzes 2000. This has caused concern over the use of sperm from subfertile men in assisted reproductive technologies (IVF and ICSI).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If DNA damage is not removed, this might lead to the formation of mutations in the germ line, or DNA damage may persist in sperm cells until after fertilization, thus affecting the developing embryo [Zenzes, 2000]. Further studies should elucidate whether GGR/NER works efficiently to protect the inherited DNA against mutation induction.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known from the literature that oxidative stress is considered to be the major pathological mechanism of tissue injury of the male reproductive tract occurring during cigarette smoking (de Jong et al, 2014;Zenzes, 2000) and excessive alcohol drinking (de Jong et al, 2014;Emanuele and Emanuele, 2001a). Allele 590A is part of the NAT2*6A haplotype, which causes the slow-acetylator phenotype due to producing proteins that are poorly expressed, unstable or possess reduced catalytic activities (Badawi et al, 1995).…”
Section: Discussionmentioning
confidence: 99%